Plasma Double Layers at the Boundary Between Venus and the Solar Wind. Issue 20 (19th October 2020) - Malaspina, D. M.; Goodrich, K.; Livi, R.; Halekas, J.; McManus, M.; Curry, S.; Bale, S. D.; Bonnell, J. W.; de Wit, T. Dudok; Goetz, K.; Harvey, P. R.; MacDowall, R. J.; et al.
Abstract: The solar wind is slowed, deflected, and heated as it encounters Venus's induced magnetosphere. The importance of kinetic plasma processes to these interactions has not been examined in detail, due to a lack of constraining observations. In this study, kinetic‐scale electric field structures are identified in the Venusian magnetosheath, including plasma double layers. The double layers may be driven by currents or mixing of inhomogeneous plasmas near the edge of the magnetosheath. Estimated double‐layer spatial scales are consistent with those reported at Earth. Estimated potential drops are similar to electron temperature gradients across the bow shock. Many double layers are found in few high cadence data captures, suggesting that their amplitudes are high relative to other magnetosheath plasma waves. These are the first direct observations of plasma double layers beyond near‐Earth space, supporting the idea that kinetic plasma processes are active in many space plasma environments. Plain Language Summary: Venus has no internally generated magnetic field, yet electric currents running through its ionized upper atmosphere create magnetic fields that push back against the flow of the solar wind. These induced fields cause the solar wind to slow and heat as the flow is deflected around Venus. This work reports observations of very small plasma structures that accelerate particles, identifiable by their characteristic electric field signatures, at the boundary where the solar wind starts to be deflected. These small plasma structures observed at Venus have been studied in near‐Earth space for decades but have never before been found near another planet. These structures are known to be important to the physics of strong electrical currents in space plasmas and the blending of dissimilar plasmas. Their identification at Venus is a strong demonstration that these small plasma structures are a universal plasma phenomena, at work in many plasma environments. Key Points: Plasma double layers are detected near the Venusian bow shock Multiple double layers are identified in a small amount of burst data Kinetic processes may help mediate interaction between the solar wind and induced magnetospheres